Corymbia citriodora extract on germination and growth of cultivated rocket (Eruca sativa L.) seedlings (Research, Society and Development, 2021)
The objective of this presente research is evaluate possible allelopathic effects of aqueous extract of eucalyptus (Corymbia citriodora) at different concentrations (0, 25, 50, 75 and 100%) on seed germination, initial growth and development of rocket seedlings (Eruca sativa L.). It was used completely randomized design (DIC), with three replications and five treatments composed of increasing doses (0, 25, 50, 75 and 100%) of eucalyptus extract, tested both in seedlings, by foliar application, and in seeds, by imbibition. The extract was produced by the cold method of turbolysis, with eucalyptus leaves crushed with water in a blender. For rocket seeds, the Germination Speed Index (IVG) and germination percentage up to 10 days after sowing (DAS) and plant height (AP) and number of leaves (NF), root length (CR) were evaluated, allometric ratio (RA). For the rocket seedlings, the variables AP, NF, CR, RA, aerial part fresh mass (MFPA), root fresh mass (MFRZ), aerial part dry mass (MSPA) and root dry mass (MSRZ) were evaluated. Statistical analysis of data was performed with the aid of the computer application SISVAR. The results of the studied variables were submitted to analysis of variance and Tukey's test at 5% probability and to regression analysis for quantitative variables, when the result of ANAVA was significant. Based on the results obtained, it was concluded that the aqueous extract of eucalyptus had no negative effect on the germination and development of rocket plants.